Analisis Kemampuan Peserta Didik Dalam Pemecahan Masalah Spldv Ditinjau Dari Kemampuan Berpikir Kreatif - Rahayu, Putri; Andri Nugroho, Aryo; Zuhri, M. Saifuddin (STAI Al-Bahjah, 2025)
Solving mathematical problems is an activity carried out by someone to overcome various difficulties that arise during the learning process. According to Polya, the problem-solving process consists of several stages, including understanding the problem, planning a strategy, implementing the chosen strategy, and reviewing the results obtained. This study to examine students’ ability to solve mathematical problems based on the level of creative thinking skills. The research uses a qualitative descriptive method and involves eighth-grade students of MTs Negeri 1 Demak, who selected based on the results of a creative thinking ability test. Data were collected through written mathematics problem-solving tasks and individual interviews to gain deeper insight into students’ thinking processes. The findings indicate that: (1) students with high creative thinking skills are able to meet all indicators of mathematical problem-solving, starting from understanding the problem to reviewing their answers; (2) students with moderate creative thinking skills are less able to review and evaluate their solutions; and (3) students with low creative thinking skills tend not to recheck their responses and often show a lack of accuracy in solving problems. These results emphasize the importance of developing students’ creative thinking abilities, as creativity significantly influences the quality of problem-solving. The study suggests that consistent practice, exposure to diverse problem types, and guided reflection can contribute to the growth of creative thinking in daily learning activities.